Biodistribution and pharmacokinetics of a telodendrimer micellar paclitaxel nanoformulation in a mouse xenograft model of ovarian cancer - Xiao W (Dove Medical Press, 2012)
Wenwu Xiao1, Juntao Luo2, Teesta Jain3, John Riggs3, Harry P Tseng1, Paul T Henderson3, Simon R Cherry4, Douglas Rowland4, Kit S Lam1,31Department of Biochemistry and Molecular Medicine, UC Davis Cancer Center, University of California Davis, Sacramento, CA; 2Department of Pharmacology, SUNY Upstate Cancer Research Institute, SUNY Upstate Medical University, Syracuse, NY; 3Department of Internal Medicine, Division of Hematology and Oncology, 4Department of Biomedical Engineering, UC Davis Cancer Center, University of California Davis, Davis, CABackground: A multifunctional telodendrimer-based micelle system was characterized for delivery of imaging and chemotherapy agents to mouse tumor xenografts. Previous optical imaging studies demonstrated qualitatively that these classes of nanoparticles, called nanomicelles, preferentially accumulate at tumor sites in mice. The research reported herein describes the detailed quantitative imaging and biodistribution profiling of nanomicelles loaded with a cargo of paclitaxel.Methods: The telodendrimer was covalently labeled with 125I and the nanomicelles were loaded with 14C-paclitaxel, which allowed measurement of pharmacokinetics and biodistribution in the mice using microSPECT/CT imaging and liquid scintillation counting, respectively.Results: The radio imaging data showed preferential accumulation of nanomicelles at the tumor site along with a slower clearance rate than paclitaxel formulated in Cremophor EL (Taxol®). Liquid scintillation counting confirmed that 14C-labeled paclitaxel sequestered in nanomicelles had increased uptake by tumor tissue and slower pharmacokinetics than Taxol.Conclusion: Overall, the results indicate that nanomicelle-formulated paclitaxel is a potentially superior formulation compared with Taxol in terms of water solubility, pharmacokinetics, and tumor accumulation, and may be clinically useful for both tumor imaging and improved chemotherapy applications.Keywords: telodendrimer, nanomicelle, paclitaxel, microSPECT/CT, imaging guided drug delivery